1990
DOI: 10.1002/jcp.1041420320
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic and motional properties of intracellular water as influenced by osmotic swelling and shrinkage of Xenopus Oocytes

Abstract: Experiments were done on fully grown Xenopus oocytes to determine the extent and the properties of cellular water of hydration. The studies involved the osmotic shrinking and swelling of the oocytes under known osmotic pressure as well as proton NMR spectral, titration, and free induction decay analyses. Studies were done both on whole oocytes and on subcellular fractions. The results show that little if any of the oocyte water in situ has the motional or osmotic properties expected of pure "bulk" water. Four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Alternatively, the swelling of the egg in liquid water is related to the gel-like properties of the capsule. Cameron and colleagues (Cameron et al, 1990) showed that about 80% of a frog egg's water is osmotically inactive, and further suggested that this water is bound to cell proteins; an idea that supports the notion of the cytoplasm being a gel. The swelling of gels does not simply depend on the difference in ionic concentration between the gel and the medium in which they are placed but on the elasticity of the polymer matrix, with the swollen gel exerting lower restraining forces on the diffusing water molecules (Yasuda et al, 1971;Gunt et al, 2007).…”
Section: Incubation In Aqueous Versus Vapour Phasesmentioning
confidence: 92%
“…Alternatively, the swelling of the egg in liquid water is related to the gel-like properties of the capsule. Cameron and colleagues (Cameron et al, 1990) showed that about 80% of a frog egg's water is osmotically inactive, and further suggested that this water is bound to cell proteins; an idea that supports the notion of the cytoplasm being a gel. The swelling of gels does not simply depend on the difference in ionic concentration between the gel and the medium in which they are placed but on the elasticity of the polymer matrix, with the swollen gel exerting lower restraining forces on the diffusing water molecules (Yasuda et al, 1971;Gunt et al, 2007).…”
Section: Incubation In Aqueous Versus Vapour Phasesmentioning
confidence: 92%
“…The reports of Cameron et al (1988b, 1997), Fullerton et al (2006b) and Fullerton and Cameron (2007) indicated that the OUW fraction can range from 1.6 to 1.7 g/g in a mammalian erythrocyte (Cameron et al, 1988a), 1.8–2.2 g/g in mammalian lens cells (Cameron et al, 1988a, 1988b), 1.3 g/g in sea urchin eggs (Merta et al, 1983), 1.2–1.7 g/g in the toad oocyte (Cameron et al, 1990) and 2.8 g/g in frog‐skeletal muscle as calculated from data of Overton (1902, cited in Ling 2006). These values and the measured total non‐bulk water fraction in rabbit skeletal muscle 2.39–3.75 g/g (Cameron et al, 2008; see Table 6) all indicate that more than half of all of cell water has non‐bulk physical properties.…”
Section: Application Of the Shm To Cellsmentioning
confidence: 99%
“…The data in Table 7 give the size of water‐of‐hydration fractions in g of water/g of DM, less extracted lipids, in the toad oocyte (Cameron et al, 1990). The extent of water in each of the hydration fractions was measured by the proton NMR titration method.…”
Section: Application Of the Shm To Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the single lipid resonance, they calculated a T 1 of 459 ± 32 ms and a T 2 of 24.44 ± 4.10 ms. In a different study, Cameron et al (14) calculated T 1 relaxation rate constants for resonance bands of defined chemical shift ranges in packed oocytes from unsuppressed spectra. A 1.8 ppm range containing the largest lipid peak gave a T 1 of 443 ± 9 ms (mean ± SEM).…”
Section: Discussionmentioning
confidence: 99%